COMPARE THE EFFECTIVENESS OF EMG BIOFEEDBACK ASSISSTED CORE STABILITY EXERCISES VERSUS CORE STABILITY EXERCISES ALONE ON PAIN AND DISABILITY IN PATIENTS WITH LOW BACK PAIN (International Journal of Physiotherapy, 2016)
Background: Low Back Pain (LBP) is a health related problem than affects 80% of the population within the age limit of 15 to 45 years. The primary treatment used for patients with LBP includes muscle strengthening along with thermotherapeutic modalities. Thus the purpose of the study is to see the efficacy of EMG biofeedback assisted core stability exercises versus core stability exercises alone in patients suffering from pain and disability.Methodology: A total of 30 patients were divided through convenient sampling method into two group- A and B. Each group had 15 patients. In Group A-SWD, traction, IFT and core stability exercises were given where as in Group B EMG biofeedback assisted core stability exercises were given for 5 treatment session per week for 2 weeks and reassessment was done on 5th and 10th day post treatment.Result: The result of the study showed that there was statistically significant (p